A Model to Minimize Costs and Promote Species Persistence under Climate Change - Alagador, Diogo (2020)
Biodiversity is severely threatened by the effects of changing climates that cause species to readjust their spatial ranges. But species are limited in their capacity to follow suitable climates, as these rearrange in space along time. Therefore, the identification of the areas to support spatial readjustments of species is a pivotal step that should be made thoroughly given the limited budgets available. We propose a two-stage mixed integer linear programming to formalize this issue, present a heuristic and report results comparing optimal and heuristic solutions.